Screening of soil fungi as bioremediation fungicide and its effect on growth of potato plants - ABDUL LATIEF ABADI; FERY ABDUL CHOLIQ; MUTHIA OKTAVIANITA; NOVIA ARINATA; MOCHAMMAD SYAMSUL HADI; YOGO SETIAWAN (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Abadi AL, Choliq FA, Oktavianita M, Arinata N, Hadi MS, Setiawan Y. 2022. Screening of soil fungi as bioremediation fungicide and its effect on growth of potato plants. Biodiversitas 23: 1605-1610. The negative impact of using fungicides on the environment can lead to chemical residues in the soil. The chemical degradation process can be carried out in several ways, one of which is by biological means by using microbes such as soil fungi. This study aimed to evaluate soil fungi isolated from natural forests for bioremediation of Mancozeb fungicide commonly used in potato fields in Indonesia. Isolated soil fungi were identified based on morphological and molecular level (PCR). The inhibition assay was carried out by growing fungal isolates on PDA media containing a fungicide with an active ingredient of 80% Mancozeb. Trichoderma harzianum isolated as a soil fungus from natural forest could grow in the fungicide Mancozeb medium. The biodegradation assay showed that treatment of Trichoderma harzianum and Mancozeb fungicide did not inhibit the growth of potato plants (plant height, number of leaves, and root length) as compared to the control. Based on the results of degradation test using HPLC method, T. harzianum both isolates can reduce the residue of fungicide Mancozeb in soil during the vegetative growth period of potato plants.